Membangun Literasi Membaca untuk Anak Usia Dini - Darmawan, Moh. Faridl; Hidayatulloh, Faisol; Ishaq, Moch. Maulana; Wicaksono, Catur; Ardianto, Mohammad Bagus; Oktaviana, Ayu Tria; Sa’diyah , Mazidah Hilmi; Sukmawati, Sayepti Dwi (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
Reading habits are an important key in self-development and the formation of broad insight, to support children's interest in reading, good facilities and infrastructure are needed, including providing learning media, providing reading parks that function as mini libraries that provide access to various reading sources for the community. The importance of reading parks and learning media lies in their role in increasing interest in reading and literacy among the community. The Kromong Village reading park which is a partner in this activity is a reading place provided by the village which used to be a knowledge and literacy center infrastructure for its residents and was also used in TPQ activities in the afternoon in the Ngusikan sub-district area. Unfortunately, as time goes by , the reading garden is no longer used. Therefore, the aim of holding activities to revitalize this reading park and providing learning media is to increase children's interest in reading in Kromong Village. Method The approach taken for community service in Kromong village is by using the PAR (Participatory Action Research) method. One of them is by applying practical methods, educator training and local community approaches so that indirectly children and the community in Kromong village can use it effectively. Facilities in the reading park. The results of the learning media that we have created. Children look more enthusiastic in accessing and using the learning media. Revitalization activities for neglected reading parks mean that reading parks can be reused by the community, especially children, as village libraries that provide more complete facilities.